Mesenteric Tumor of an Infant: A Clinical and Pathological Surprise - Osama, Md Ali; Singh, Smita; Prajapati, Sahaj; Choudhury, Subhasis Roy; Amina, Nishat (Annals of Pathology and Laboratory Medicine, 2022)
Inflammatory myofibroblastic tumor (IMT) is a tumefactive proliferation of spindled myofibroblastic cells admixed with inflammatory infiltrate. This tumor has a predilection for pulmonary location and also involves visceral soft tissues in children and adults. Tumors in extrapulmonary locations like abdomen, mesentery, bowel, head & neck, genitourinary and musculoskeletal are more aggressive locally and mimic malignancy. IMTs from colon are very rare and are treated by surgical excision. We report a case of a 9-month old female with IMT of sigmoid colon with no bowel complaints, treated by complete surgical excision with no further treatment needed.